Penerapan Terapi Myra E Levine Melalui Aplikasi Tehnik Relaksasi Otot Progresif Terhadap Intensitas Nyeri Pada Kasus Rematik Di Puskesmas Bermani Ulu Kabupaten Rejang Lebong - Oktaviani, Ayu; Tranado, Hengki; Handayani, Tita Septi (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Rheumatoid Arthritis is a progressive, systematic and chronic inflammatory disease that initially affects the synovial joints accompanied by edema, congestion of vascular exudate and cellular infiltration (Risnanto & Isnani, 2014). The impact of Rheumatoid Arthritis can cause discomfort, pain and limited physical mobility so that there is a risk of disability and loss of movement (Elviani et al., 2021). Progressive muscle relaxation therapy is a muscle stretching and breathing exercise that is done to produce a response that can reduce sympathetic nerve activity so that it can reduce pain. The general purpose of this case study is to apply Myra E Levine's nursing theory to Rheumatic Patients by performing and teaching Progressive Muscle Relaxation Techniques to reduce pain intensity, this study was also conducted to determine whether Myra E Levine's theory can be applied to Rheumatic patients by providing Progressive Muscle Relaxation Technique therapy. This case study method is a qualitative method with a Case study research strategy. The type of case study when carrying out nursing care is Case study research by applying Myra E Levine's nursing model theory to patients suffering from Rheumatic. The results of nursing care for Rheumatic patients using Myra E Levine's nursing theory include: Assessment, Tropihicognosis Decisions, hypotheses and compiling interventions, implementation and evaluation of nursing. Tropihicognosis Decision, found in patients namely Chronic Pain (related to the inflammatory process) and Anxiety (related to changes in health status. While the hypothesis and nursing interventions that are compiled are directed at helping to reduce pain intensity with Progressive Muscle Relaxation Technique therapy through the Conservation Model approach.Myra E Levine's nursing model theory can be applied and applied well in nursing focusing on Rheumatism cases. Suggestions for health workers are for Progressive Muscle Relaxation Technique therapy in patients with rheumatism to reduce pain intensity so as to increase mobilization ability and reduce activity disorders due to uncontrolled pain.